Avaliando a atuação dos deputados evangélicos na Câmara dos Deputados : comportamento partidário ou religioso? - Cassotta, Priscilla Leine (Universidade Federal de São Carlos, 2016)
Since the democratization of the country, evangelicals are significantly expanding its performance spaces in Brazilian society. Contrary to the image that the Gospel does not mix politics, began to launch their own applications, with great visibility from the elections to the Constituent Assembly in 1986. However, despite the presence of evangelical parliamentarians in party politics, there isn't in Brazil an evangelical party. That is, the demands of evangelical groups in Brazil are not channeled by a single party. Thus, this research has the objective to assess to what direction the evangelical parliamentary has guided its actions in the Chamber of Deputies of Brazil. More precisely, we seek to answer the following questions: what is the nature of the main Law of projects presented by the Gospel representative? As the evangelical deputy has expressed its preference on roll calls, according to the party or closer to the religious convictions? Our hypothesis is that evangelicals Members do not form a cohesive group and nonpartisan, so send Law projects and vote according to their political party. We will analyze the propositions of these deputies and roll calls of the following legislatures: 53 (2007- 2011) and part of 54 (2011-2014).
Keywords: Representação política; Partidos políticos; Deputados evangélicos; Political representation; Political parties; Evangelical members; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA URBANA